English Malay maritime words in the Malay seas - Zarina Othman (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malay was once the lingua franca for the Malay Archipelago region, i.e. the Nusantara sphere and beyond. The Malay had been used widely by traders and seamen as the language of trade and commerce. It illustrates the richness of Malay in its nautical and maritime words throughout the pre-modern era, which indirectly led to the positioning of Malaysia as a maritime nation at that point in time. This paper explores Malay words through investigative evidence of words used in the Malay world's seas, where historically, the peninsula was the focus of trade and commerce for the Nusantara region. An investigation to seek evidence of nautical words was conducted on the Malay glossaries in two historical writings. The primary source of analysis was the Shellabear English Malay Dictionary (1916), with the Malacca Maritime Code of the Malays (Stamford Raffles, 1879) as another source of analysis to supplement the findings on Malay as the maritime language. The dictionary is composed of 614 pages with 7000 Malay words and phrases that had equivalence to English nautical words and an appendix of household, nautical and medical terms, among others. A manual calculation shows that Shellabear had 109 'nautical terms' entries in this English–Malay translated dictionary. The maritime nature of the Malay world in both texts reflects many terms related to seafaring, fishing, trade, and navigation, with a prevalence of different types of boats, fishing equipment, and navigation techniques.